Analisis Kinerja Jaringan Irigasi Pada Delapan Daerah Irigasi Yang Tersebar Di Kota Kupang - yosefina Susriyati; Wilhelmus Bunganaen; Ruslan Ramang (Universitas Nusa Cendana, 2023)
Kupang City has eight irrigation areas, namely Amnesi (36 Ha), Batuplat (90 Ha), Labat (20 Ha), Belo (60 Ha), Fatukoa (220 Ha), Oelon (50 Ha), Oepura (65 Ha). and Kolhua (20 Ha). During operation, the irrigation network was damaged. This study aims to determine the performance of the irrigation network from the physical aspect, utilization, and aspects of operation and maintenance. This study uses a qualitative method by measuring the discharge and quantitative methods by observing the physical condition of the channel and analyzing the answers to the questionnaire. The performance of the irrigation network from the physical aspect was obtained in good condition with an average score of 3.55 being Oelon and Labat, a fairly good condition with an average score of 2.90 being Belo, Batuplat, Amnesi and Fatukoa 4, poor condition with a score of 2.45 being Oepura, and very unfavorable with a score of 1.00 is Kolhua. The performance of the irrigation network from the utilization aspect was obtained in fairly good condition with an average value of 2.68, namely Belo, Batuplat, Oelon, Labat, Amnesi, Oepura, Amnesi and Fatukoa 4, in poor condition with a value of 1.56, Kolhua. The performance of the irrigation network from the aspect of operation and maintenance is obtained in fairly good condition with a value range of 2.80 is Belo, Batuplat, Oelon, Labat, Amnesi, Oepura, Amnesi and Fatukoa 4 and in very poor condition with a value of 1.19 is Kolhua.